Quay Layout Planning Of Beaco Port Viqueque District, Timor-Leste - Muhamad Kemal Idris; Benny Heriyanto; Nilton Fernandes; Marito Menezes; Wahyu Adi Setyaningsih (Journal of Applied Geospatial Information, 2026)
Timor-Leste shares the island of Timor with Indonesia and is strategically located near Australia, giving it significant maritime potential for both domestic connectivity and international shipping logistics. To support maritime transportation and national economic growth, the Government of Timor-Leste, through the Ministry of Transport and Communications, plans to develop and upgrade several port facilities, including Beaco Port. Therefore, a jetty layout plan that meets technical planning standards and operational requirements is required. This study focuses on the planning and design of a jetty structure for vessels with a capacity of 1000 DWT. The planning process includes site selection, determination of quay type and dimensions, quay basin, navigation channel, turning basin, causeway dimensions, fender and bollard specifications, as well as the spacing between fenders and bollards. The analysis was conducted using several software packages, including Microsoft Excel, WR Plot, ODV (Ocean Data View), MIKE Zero, and AutoCAD. The results indicate that Site 2, located at coordinates 8°56'53.43” S and 126°28'2.08” E, was selected as the optimal location. The proposed design consists of a jetty-type quay with dimensions of 122.6 m in length and 32.5 m in width, a one-way navigation channel with a depth of 10 m, width of 46.4 m, and length of 200 m, a turning basin with a diameter of 201 m, and a jetty basin with a depth of 6 m, length of 100.5 m, and width of 20 m. The selected fender type is V-SAN 800H × 1000L with 10 m spacing between fenders and WF500 fender piles, while the bollard system uses TEE BOLLARD with a capacity of 100 kN and 15 m spacing between bollards.